Gender Perspective Learning Methods: An Alternative in Learning Drama Appreciation for Students - Syofiani, Syofiani; WS, Hasanuddin; Ramadhan, Syahrul; Isnanda, Romi (Proceedings of the UR International Conference on Educational Sciences, 2018)
This article describes issues related to gender perspective learning methods. Theaimed of this study is to improve drama appreciation learning for students. In the learningprocess of drama appreciation with a gender perspective, it gives students an understanding thatthe position and role of men and women in various family and community life are consideredthe same. The components that are the focus of the discussion in this article are namely theessence and the characteristics of drama appreciation learning and learning methods ofappreciation of innovation drama thus the students feel they have new insights in the learningprocess, especially in drama appreciation learning. The students not only understand drama as aliterary and performing arts, but they also understand that gender issues are something that canbe used as a reference or model in drama appreciation learning. In learning process, the lecturershould also be able to choose or obtain the drama texts that place the position of women at leastequal to men.